Effective treatment of low-risk acute GVHD with itacitinib monotherapy - Etra, Aaron; Capellini, Alexandra; Alousi, Amin; Al Malki, Monzr M.; Choe, Hannah; DeFilipp, Zachariah; Hogan, William J.; Kitko, Carrie L.; Ayuk, Francis; Baez, Janna; Gandhi, Isha; Kasikis, Stelios; et al. (Blood, 2023)
The standard primary treatment for acute graft-versus-host disease (GVHD) requires prolonged, high-dose systemic corticosteroids (SCSs) that delay reconstitution of the immune system. We used validated clinical and biomarker staging criteria to identify a group of patients with low-risk (LR) GVHD that is very likely to respond to SCS. We hypothesized that itacitinib, a selective JAK1 inhibitor, would effectively treat LR GVHD without SCS. We treated 70 patients with LR GVHD in a multicenter, phase 2 trial (NCT03846479) with 28 days of itacitinib 200 mg/d (responders could receive a second 28-day cycle), and we compared their outcomes to those of 140 contemporaneous, matched control patients treated with SCSs. More patients responded to itacitinib within 7 days (81% vs 66%, P = .02), and response rates at day 28 were very high for both groups (89% vs 86%, P = .67), with few symptomatic flares (11% vs 12%, P = .88). Fewer itacitinib-treated patients developed a serious infection within 90 days (27% vs 42%, P = .04) due to fewer viral and fungal infections. Grade ≥3 cytopenias were similar between groups except for less severe leukopenia with itacitinib (16% vs 31%, P = .02). No other grade ≥3 adverse events occurred in >10% of itacitinib-treated patients. There were no significant differences between groups at 1 year for nonrelapse mortality (4% vs 11%, P = .21), relapse (18% vs 21%, P = .64), chronic GVHD (28% vs 33%, P = .33), or survival (88% vs 80%, P = .11). Itacitinib monotherapy seems to be a safe and effective alternative to SCS treatment for LR GVHD and deserves further investigation.
CRIS-Team Scopus Importer:2023-02-03